APLIKASI TES MINAT BAKAT SERTA REKOMENDASI JURUSAN UNTUK SISWA SMA MENGGUNAKAN METODE FORWARD CHAINING - Nurul Husna; Munirul Ula; Yesy Aflillia (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
In the Industrial Revolution 4.0 era, human resources play a crucial role in workplace competitiveness, requiring individuals to develop their skills and knowledge through education. High school graduates who wish to pursue higher education face difficulties in choosing the right major. This situation is influenced by external pressures, causing many students to make choices that are not in line with their abilities. This study aims to develop an Interest and Talent Test Application to facilitate high school students in providing explanations about their interests and talents as well as recommendations for appropriate majors. This application is built on a website using the Multiple Intelligences theory and the Forward Chaining method. In this process, data samples will be used to test the methods used in this study. The samples used came from 60 students of SMA Negeri 1 Jeumpa who had completed the trial. The results of this test showed that the average type of intelligence of students in the high school was Verbal (Linguistic) intelligence for 16 students with majors that correspond to their type of intelligence, namely Communication Science, Language and Literature, International Relations, Law, and Political Science. This system has achieved an average user satisfaction rating of 81.91%, indicating that users are satisfied with consulting using this aptitude and interest testing application.